СТАН, ПРОБЛЕМИ ТА ПЕРСПЕКТИВИ ТРАНСФОРМАЦІЇ ВІЙСЬКОВОЇ ОСВІТИ В КОНТЕКСТІ РЕАЛІЗАЦІЇ СТАНДАРТІВ НАТО - КЛАЧКО, Володимир; БІЛЯВЕЦЬ, Сергій; ДІДЕНКО, Олександр; ДЕМ’ЯНЮК, Юрій (Zbirnyk naukovykh prat͡s︡ʹ Nat͡s︡ionalʹnoï akademiï Derzhavnoï prykordonnoï sluzhby Ukraïny. Serii͡a︡: pedahohichni nauky, 2022)
The article presents the results of research, publications, and regulations that reveal the current situation, problems, and prospects for the transformation of military education in the context of the implementation of NATO standards. It has been found that improving the system of military education is relevant, since it is an important component of the security and defense sector of Ukraine and provides the Armed Forces, other military formations and individual components of the security and defense sector, in particular the National Guard of Ukraine and the State Border Guard Service of Ukraine, with officer personnel. The peculiarity of Ukraine’s military education system is that it is integrated into the nationwide system of education and is regulated by both normative documents on general education and departmental normative legal acts. Transformation of military education in the context of the implementation of NATO standards involves the creation of a single unified system of training for the defense forces, taking into account the experience of NATO member states and achieving interoperability with the armed forces of these states, as well as the formation of an effective system of professional military education, integrated into the state system of education. A study of the professional military education systems of NATO member countries shows that although they appear to be similar, they have a number of significant differences in terms of professional military training and education, the timing of education or training. For Ukraine, as well as for the European countries of NATO, it is characteristic that educational programs are built on the European credit transfer system (ECTS), which is characterized by a three-levelsyst em of higher education. Therefore, under current conditions, it is important to combine and take into account in the military education system both the requirements of the European credit-transfer system and the regulations and rules stipulated by NATO standards. It has been found that the transformation of military education in the context of the implementation of NATO standards can be accompanied by certain negative phenomena, which should be taken into account at the stage of development and justification of the concept of military education and its normative support. In the process of transformation of military education in the context of  the implementation of NATO standards, it is important to take into account the specifics of the functioning of the individual components of the security and defense sector. У статті узагальнено результати досліджень, публікацій та нормативно-правових актів, у яких розкриваються стан, проблеми та перспективи трансформації військової освіти в контексті реалізації стандартів НАТО. З’ясовано, що удосконалення системи військової освіти є на часі, оскільки вона є важливим компонентом сектору безпеки і оборони України і забезпечує Збройні Сили, інші військові формування та окремі складові сектору безпеки та оборони, зокрема Національну гвардію України та Державну прикордонну службу України, офіцерським складом. Особливістю системи військової освіти України є те, що вона інтегрована у загальнодержавну систему освіти і регулюється як нормативними документами з питань загальної освіти, так і відомчими нормативно-правовими актами. Трансформація військової освіти в контексті реалізації стандартів НАТО передбачає створення єдиної уніфікованої системи підготовки персоналу для сил оборони з урахуванням досвіду держав-членів НАТО та досягнення сумісності зі збройними силами цих держав, а також формування ефективної системи професійної військової освіти, яка інтегрована в державну систему освіти. Дослідження систем професійної військової освіти країн-членів НАТО показує, що за зовнішньої схожості вони мають низку суттєвих відмінностей щодо поєднання професійної військової підготовки та освіти, термінів здобуття освіти або проходження підготовки. Для України, як і для європейських країн-членів НАТО, характерним є те, що освітні програми побудовані на європейській кредитно-трансферній системі (ECTS), для якої характерними є триступенева система вищої освіти. Тому за нинішніх умов важливим є поєднання і врахування в системі військової освіти як вимог європейськоїкредитно-трансферної системи, так і норм і правил, передбачених стандартами НАТО. З’ясовано, що трансформація військової освіти в контексті реалізації стандартів НАТО може супроводжуватися певними негативними явищами, що потрібно врахувати на етапі розробки та обґрунтування концепції військової освіти та її нормативного забезпечення. У процесі трансформації військової освіти в контексті реалізації стандартів НАТО важливо врахувати також особливості функціонування окремих складових сектору безпеки і оборони.